Las jóvenes generaciones contemporáneas - Eduardo González Calleja (Mélanges de la Casa de Velázquez, 2004)
The article seeks to give an overview of the ways in which the various human sciences —particularly philosophy and political sociology— have interpreted contemporary generational conflict since the 1920s and 1930s, while describing the evolution and the growing complexity of forms of protest as they relate to gradual acquisition of historical and political consciousness by juvenile cohorts. It examines various archetypes exemplifying such modes of conflictive political participation: student rioting, party militancy, paramilitary activism and the new alternative social movements.